Factors affecting children's HPV vaccination in Austria: Evidence from a parent survey - Madeleine Waser; Raffael Heiss; Wegene Borena (Taylor & Francis Group, 2022)
Human papillomavirus (HPV) is a sexually transmitted infection that causes cervical cancer, head and neck cancer, other urogenital cancers, and genital warts. In Austria, where HPV vaccination is free for children, the vaccination rate nevertheless remains insufficient for herd immunity against HPV. Using a cross-sectional survey of parents (N = 334) in the state of Tyrol, Austria, we examined parents' reasons for rejecting children's HPV vaccination and key predictors of vaccination intention for their children, including knowledge about HPV, attitude toward vaccination, sources of information about the HPV vaccine, socioeconomic factors, and HPV vaccination intention. Data analyzed using descriptive statistics and logistic regression modeling revealed an overall 81.9% acceptance rate of HPV vaccination. The most common reasons for vaccine hesitancy were a fear of side effects, a perceived lack of information, and the perception that children are too young to be vaccinated. A high level of knowledge about HPV was significantly associated with vaccine acceptance for female but not male children. Negative attitude toward vaccination was significantly related to lower vaccine acceptance, and parents who reported informing themselves about HPV vaccination from online sources were less likely to accept vaccination. Such results call for more educational measures to reduce misinformation about HPV vaccination and thereby reduce the fear of its side effects and promote early vaccination. More information is also needed to improve parents' attitude toward and their knowledge about vaccination, the dissemination of which should focus on the benefits of vaccines for children of both sexes.